2010
DOI: 10.1074/jbc.m109.055475
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phagocytosis in Macrophages by Neuraminidase 1

Abstract: The differentiation of monocytes into macrophages and dendritic cells is accompanied by induction of cell-surface neuraminidase 1 (Neu1) and cathepsin A (CathA), the latter forming a complex with and activating Neu1. To clarify the biological importance of this phenomenon we have developed the gene-targeted mouse models of a CathA deficiency (CathA S190A ) and a double CathA/Neu1 deficiency (CathA S190A-Neo ). Macrophages of CathA S190A-Neo mice and their immature dendritic cells showed a significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 39 publications
1
86
1
Order By: Relevance
“…Increased neuraminidase activity was previously suggested as the most probable mechanism (20). It was recently shown that neuraminidase activity increases in sepsis which leads to erythrocyte desialylation (35) and that neuraminidase 1, one of the four human neuraminidases, has an important role in the immune response and inflammation (36)(37)(38)(39). However, the present re- sults show that, in contrast to transferrin, total plasma proteins do not show a decrease in their sialylation levels.…”
Section: Discussioncontrasting
confidence: 55%
“…Increased neuraminidase activity was previously suggested as the most probable mechanism (20). It was recently shown that neuraminidase activity increases in sepsis which leads to erythrocyte desialylation (35) and that neuraminidase 1, one of the four human neuraminidases, has an important role in the immune response and inflammation (36)(37)(38)(39). However, the present re- sults show that, in contrast to transferrin, total plasma proteins do not show a decrease in their sialylation levels.…”
Section: Discussioncontrasting
confidence: 55%
“…In another study, Neu1 was found to negatively regulate lysosomal exocytosis in hematopoietic cells where it processes the sialic acids on the lysosomal membrane protein LAMP-1 [24]. More recently, evidence is provided to suggest that cell surface Neu1 also activates phagocytosis in macrophages and dendritic cells presumably through the desialylation of multiple receptors, including Fc receptors for immunoglobulin G (FcγR) [58].…”
Section: Discussionmentioning
confidence: 97%
“…This suggests the action of a cell surface-linked sialidase like Neu-3 (18) or the reportedly surface associated Neu-1 (19). Antisera directed against peptides of Neu-1 and Neu-3 diminished surface-associated sialidase activity (not shown).…”
Section: Discussionmentioning
confidence: 99%